117k views
3 votes
Find r if 3(r - 7) = 4(2 - 2r) + 4

User Xiaopo
by
4.3k points

2 Answers

3 votes

Answer:

Explanation:

3(r - 7) = 4(2 - 2r) + 4

3r+(-21)=8+(-8r)+4

-21+8+4=3r+(-8r)

-9=-5r

User Kevin Lynx
by
4.5k points
0 votes

Answer:

r=3

Explanation:

3(r - 7) = 4(2 - 2r) + 4

Distribute

3r -21 = 8 -8r +4

Combine like terms

3r -21 = 12 -8r

Add 8r to each side

3r +8r-21 = 12 -8r+8r

11r -21 = 12

Add 21 to each side

11r -21+21 =12+21

11r = 33

Divide each side by 11

11r/11 = 33/11

r = 3

User Giammin
by
4.9k points